Opportunities for learning LEAP Essential Learning Outcomes: a classroom ethnography of an undergraduate Shakespeare through Performance course - Went, Jeanine Belcastro, author; Kuk, Linda, advisor; Jennings, Louise, committee member; Jones, Laura, committee member; Kindelan, Nancy, committee member (Colorado State University. Libraries, 2016)
The purpose of this classroom ethnography was to explore what opportunities for learning, aligning with LEAP Essential Learning Outcomes (ELO) categories, could be found in an upper-level theatre course for theatre majors at a small, selective, baccalaureate degree granting institution in the Northeastern United States. Using ethnographic data collection methods, the study explored how participation in an upper level theatre course supported or did not support the construction of opportunities for learning the LEAP ELO categories. Findings indicated that opportunities for learning LEAP ELO were supported in three major ways: sense of community, word work, and classroom engagement. Results demonstrated that participation in an upper-level theatre course supported opportunities for learning fourteen of the sixteen LEAP ELO in the course, representing all four LEAP ELO categories: knowledge of human cultures and the physical and natural world, integrative and applied learning, intellectual and practical skills, personal and social responsibility.